1988
DOI: 10.1136/jech.42.1.66
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for increasing compliance within a general practitioner based screening project for colorectal cancer and the effect on practitioner workload.

Abstract: Colorectal cancer is the second most common cause of death from malignant disease in England and Wales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
(2 reference statements)
2
25
0
Order By: Relevance
“…Nicholls et al (1986) compared different methods of invitation to do a Haemoccult test and found that acceptance was greatest (57%) among people offered the test during a consultation with their general practitioner, but was only 38% when the test was sent by post. Inclusion of an educational leaflet made no difference, a fact also confirmed in Nottingham (Pye et al, 1988). In Dijon, administration of the test by a doctor also achieved higher response (57%) than when it was mailed (40%).…”
supporting
confidence: 48%
“…Nicholls et al (1986) compared different methods of invitation to do a Haemoccult test and found that acceptance was greatest (57%) among people offered the test during a consultation with their general practitioner, but was only 38% when the test was sent by post. Inclusion of an educational leaflet made no difference, a fact also confirmed in Nottingham (Pye et al, 1988). In Dijon, administration of the test by a doctor also achieved higher response (57%) than when it was mailed (40%).…”
supporting
confidence: 48%
“…[14][15][16][17] However, those studies failed to show a consistent increase in participation, perhaps because advance notification letters were accompanied by educational material or the effect was masked by other barriers to participation associated with guaiac FOBTs. Using an advance notification letter with low information burden, coupled with removal of diet and medication barriers through the use of immunochemical tests, may allow the positive effect of advance notification to become evident.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] While most studies showed that this was associated with increased uptake, it was often administered together with educational materials and so the effect alone is unclear. Advance notification has never been trialled in programmes using faecal immunochemical tests (FIT) where several barriers to participation are reduced.…”
Section: Advance Notification Of Invitationmentioning
confidence: 99%
“…On one end of the spectrum, these features are externally imposed on participating organizations/subjects, such as providing physicians with fl ow sheets, 1,2 checklists, 3,4 or computer-based reminders, [5][6][7][8] or distributing patient educational materials. 6,9,10 Although such approaches can provide straightforward change mechanisms that ensure generalizability and treatment fi delity, they can pose problems when contextual variables contradict intervention fi delity 11 or when motivation to sustain changes wanes once the researchers leave. cesses for change emerge internally.…”
Section: Introductionmentioning
confidence: 99%